Attractivity and palatability of different hydrolysed proteins for the ornamental species Betta splendens (Regan, 1910) - de Oliveira, Suzana Raquel; Alves, Denis Rogério Sanches; Marques Gomes, Ricácio Luan [UNESP]; Hattori, Jahina Fagundes de Assis; Signor, Altevir; Boscolo, Wilson Rogério; Bittencourt, Fábio (Hindawi, 2022)
The objective of this study was to define attractivity and palatability of juvenile Betta splendens when fed diets containing tilapia meal (TM) and a 5% inclusion of different protein sources: chicken protein hydrolysate (CPH), porcine liver protein hydrolysate (PLH), feather protein hydrolysate (PHP) and porcine mucosa protein hydrolysate (PMH). Five juveniles were utilized with an average weight of 2.92 ± 0.24 g, and an average length of 3.24 ± 0.39 cm. Feeding management was determined via random drawings of both specimens and feed type, with a feeding schedule of four times per day, in which feeding habits were observed regarding the time of capture of the first pellet, number of pellet rejections, number of approaches without pellet capture and number of pellets consumed. The data were submitted to ANOVA, and, subsequently, Duncan's test was performed with a 5% significance. The greatest index of attractivity and palatability was encountered with PLH at 17.14%. The significant effect (p < 0.05) was observed in the feeding behaviour regarding the consumption of pellets. Thus, PLH may be utilized to effectively increase consumption in Betta splendens juveniles as a substitute to tilapia meal and as a means of reducing feed waste in aquariums of this species.
Keywords: alternative ingredients; animal nutrition; feeding behaviour; ornamental fish